One last shot - Anderson, John David, 1975- (Walden Pond Press, 2020)
Malcolm does not enjoy sports and feels that he does not live up to his father's expectations because of his lack of interest. When he decides to start playing miniature golf, Malcolm discovers a sport that he enjoys, but soon his dad is signing him up for lessons and tournaments. When tension between his parents reaches the breaking point, Malcolm is not sure of anything in his life.